2001
DOI: 10.1001/jama.286.4.436
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Passive Smoking on the Coronary Circulation in Healthy Young Adults

Abstract: Passive smoking substantially reduced CFVR in healthy nonsmokers. This finding provides direct evidence that passive smoking may cause endothelial dysfunction of the coronary circulation in nonsmokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
231
0
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(254 citation statements)
references
References 41 publications
8
231
0
6
Order By: Relevance
“…Although SHS causes over 10 times as many deaths from heart disease as from lung cancer, no attempt has been made to set a level of SHS to protect from heart disease and other adverse effects of SHS. The adverse cardiovascular effects of SHS do not require years of exposure, but can occur following short exposures (Glantz and Parmley, 2001;Otsuka et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although SHS causes over 10 times as many deaths from heart disease as from lung cancer, no attempt has been made to set a level of SHS to protect from heart disease and other adverse effects of SHS. The adverse cardiovascular effects of SHS do not require years of exposure, but can occur following short exposures (Glantz and Parmley, 2001;Otsuka et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These figures generate major concerns given the overwhelming evidence on the adverse health effects of SHS (26) together with recent reports showing that, despite currently adopted measures, the prevalence rates of smoking are increasing (30). Experimental data from our (17) and other (14,18,19,26) laboratories suggest that even brief exposures to SHS cause marked changes in thyroid hormone secretion, platelet aggregation, endothelial function, arterial pressure waveform, inflammatory markers, as well as other hemodynamic alterations involved in the development of ischemic heart disease. At least some of these effects appear to be more pronounced in men compared with women (14, 20), but the mechanism underlying this phenomenon has yet to be elucidated.…”
mentioning
confidence: 86%
“…There is no evidence that there is a safe level of exposure to ETS, 8 however, and studies have indicated that even brief exposures can adversely affect non-smokers. 9 For example, Otsuka and colleagues reported significant changes in endothelial function among healthy young non-smokers after just 30 minutes of exposure to ETS; function decreased to that found in habitual smokers. 9 ETS incursions might be particularly harmful in homes with young children, since children are more vulnerable to the effects of ETS because of their higher relative ventilation rates which lead to a higher intake of smoke.…”
mentioning
confidence: 99%
“…9 For example, Otsuka and colleagues reported significant changes in endothelial function among healthy young non-smokers after just 30 minutes of exposure to ETS; function decreased to that found in habitual smokers. 9 ETS incursions might be particularly harmful in homes with young children, since children are more vulnerable to the effects of ETS because of their higher relative ventilation rates which lead to a higher intake of smoke. 10 Because interventions to decrease ETS exposure in the home are controversial, it is important to gauge current official smoking policies in apartment buildings and apartment dwellers' attitudes concerning smoking in public areas and their own policies regarding smoking in their units.…”
mentioning
confidence: 99%